Assessing Monthly Progress towards Annual Fiscal Revenue Targets - Kanda, Daniel (IMF Working Papers; Working Paper ;, 2002)
A simple statistical methodology is developed to help evaluate monthly progress toward an annual fiscal revenue target, and the applicability of the methodology to both developing and industrial countries is demonstrated using data for Sri Lanka and the United States.